The global diffusion of human resource practices institutional and cultural limits - Lawler, John J.; Hundley, Greg (Emerald JAI, 2008)
The competitive forces generated by globalization act to promote the cross-national diffusion of human resource management 'best practices'. In particular, high performance work practices have come to be viewed as the standard as companies in many parts of the world have endeavored to 'Americanize' their employment and management systems. Yet cultural, institutional, and ideological forces continue to offer resistance to the global convergence of HR practices. This volume contains papers from authors in Europe, Asia, Africa, and US who explore diffusion in a variety of national contexts. Different methodologies and perspectives provide a range of interpretations regarding diffusion and convergence.
Keywords: Personnel management.; Management.; Personnel & human resources management.; Business & Economics -- Human Resources & Personnel Management.; elektronické knihy; electronic books